Potential Application of Plant-Based Functional Foods in the Development of Immune Boosters - Jiang, Linlin; Zhang, Guoqing; Li, Ye; Shi, Guirong; Li, Minhui (Frontiers in Pharmacology, 2021)
The immune system is one of our most complex biological systems in the body. The immune system dysfunction is responsible for various diseases like cancer and other infectious diseases. So modulation of immune responses to much required for controlling the various infectious diseases. At present, the use of a variety of agents to enhance immunological and host defenses mainly by increasing the humoral antibody responses, enhancing the phagocytic activity of macrophages or modifying the cell-mediated immune response. However, synthetic drugs can have side effects in treatment. Thus, the search for natural products of plant origin as new leads for the development of potent and safe immune booster is gaining much major research interest. According to the report that plant-based functional foods have wide immunomodulatory effects and influence on the immune system of the human body. The current comprehensive review figure outs the use of bioactive compounds from plant-based functional foods as a natural immune booster. At the same time, we explore potential mechanisms of bioactive compounds from plant-based functional foods as a natural immune booster. The immune enhancement has a good prospect in disease prevention and treatment and is worthy of further research and development with modern science and technology.